A Change of Circumstances and Contract Adjustment: Indonesian Law and Beyond - Cahyono, Akhmad Budi; Pangaribuan, Togi Marolop Pradana; Raumanen, Vivika Dyatri (Universitas Negeri Semarang, 2025)
In the case of long-term contracts, parties might find it challenging to anticipate the relevant state of affairs that may affect the performance of the contract in the future or any change of circumstances. This paper argues that implementing a change of circumstances doctrine that allows the disadvantaged party to demand contract adjustment has been applied since long ago in Indonesia. This application is particularly evident when it comes to changes in currency. The principle of justice becomes the main consideration for the judges to make contract adjustments due to changes in circumstances. However, some court decisions accepted such requests for contract adjustment due to a change in circumstances, even though it was based on a force majeure defense. In order to provide legal certainty in the future, it is highly recommended that legislators separate the rules of force majeure from the rules of change of circumstances.